The Correlation of Reward and Punishment Toward Writing Achievement Among The Students of MAN 2 Kediri - Nur Aida Laila Fitriana; Erwin Hari Kurniawan (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Kadiri, 2022)
The purpose of this study is to determine the correlation of reward and punishment toward writing achievement among the students of MAN 2 Kediri. This study aims to find out questions of problem, namely (1) to find out the correlation between reward and writing achievement among students of MAN 2 Kediri, (2) to find out the correlation between punishment and writing achievement among students of MAN 2 Kediri, (3) to find out the correlation between reward and punishment towards writing achievement among the students of MAN 2 Kediri. This study uses a quantitative approach. To collect data, researchers used correlation methods and questionnaire data collection techniques. The results of the research are: there is a significant correlation between X1, X2 and Y with a value of 11,942. Then Ha is accepted and it can be concluded that there is a simultaneous correlation between X1 and X2 with Y. Based on the results of the research is a correlation between reward and punishment for writing achievement. Then it is necessary to : (1) For teachers, this study is expected to provide knowledge to teachers that reward and punishment affects writing achievement, (2) For students, it is hoped that students can understand that the task of a student is to follow every series of education, (3) For future researchers, this research is expected to be a reference for further research.